Relationship Between Direct Aggression and Prosocial Behavior: The Role of Attention and Intelligence Among Children at Risk for Behavioral Problems - Chiodi, Sofia Lira; Lúcio, Patrícia Silva [UNESP]; Ilari, Beatriz; Germano, Nayana Di Giuseppe; Cogo-Moreira, Hugo; Bortz, Graziela [UNESP] (Springer Nature, 2024)
This study aimed to investigate the influence of attention and intelligence in the prediction of prosocial behavior by direct aggression (proactive or reactive) in school-aged children at risk for behavioral problems. The sample was composed of 64 children aged 6 to 8 years screened for risk of behavioral problems, who were enrolled in a clinical trial. Multiple regression models were tested to investigate the prediction of prosocial behavior by direct aggression (proactive or reactive), attention, and intelligence. Additive multiple moderation models were tested to analyze the conditional effect of attention and intelligence in the prediction of prosocial behavior by proactive and reactive aggression. Aggression (proactive or reactive), attention, and intelligence did not linearly predict prosocial behavior. Conditional effects were found only for the proactive aggression model. Negative impacts on prosocial behavior were observed among children with low attention and high intelligence performance, while medium and high levels of attention showed to be protective factors among low to medium intellectual ability children. Clinical impacts of the results are discussed.
Keywords: Attention; Direct aggression; Intelligence; Moderation; Prosocial behavior